Engineering batch and pulse refolding with transition of aggregation kinetics: An investigation using green fluorescent protein (GFP). (28th July 2015) - Pan, Siqi; Odabas, Nora; Sissolak, Bernhard; Imendörffer, Moritz; Zelger, Monika; Jungbauer, Alois; Hahn, Rainer
Abstract: Pulse refolding is a strategy to overcome concentration dependent aggregation, assuming that aggregation is significantly suppressed under diluted conditions. When a typical 2nd or higher order aggregation kinetics is assumed, kinetics over predicted yields at low refolding concentrations. Using GFP as our model protein, we found a transition in aggregation kinetics from 2nd to 1st order when intermediates deplete from 100 to 60 µg/ml. Taking this transition into account, the model can better predict refolding yields in batch and pulse refolding strategies. This model is suited for the design of refolding processes since this deviation from 2nd or higher order aggregation was also previously observed in other proteins. Highlights: Aggregation transits from 2nd to 1st order as intermediate depletes during refolding. Better prediction in batch and pulse refolding using proposed transition model. Native model protein (sGFPmut3.1) does not aggregate with intermediates. Potential engineering tool to optimize in vitro refolding in bioprocess settings.